OGYGES AND VETURIUS (COLEOPTERA: PASSALIDAE) IN CENTRAL AMERICA: SYNONYMIES, RANGE EXTENSIONS AND NEW SPECIES - Schuster, Jack C.; Cano, Enio B.; Boucher, Stéphane (Instituto de Ecología, A.C., 2005)
The following nomenclatural changes in passalid taxonomy are made: Veturius laevior (Kaup 1868) n.stat., bona sp.; V. lineatosulcatus Luederwaldt 1941, n. syn. of V. laevior; Ogyges championi (Bates 1886) n. stat., bona sp.; and O. laevior (Kaup 1868) sensu auct., n. syn.of O. championi. New distribution records are given for V. sinuatocollis Kuwert 1890 (Honduras), O. crassulus (Casey) (Guatemala, Honduras), O. championi, O. cakchiqueli Schuster & Reyes-Castillo 1990, O. tzutuhili Schuster & Reyes-Castillo 1990, O. hondurensis Schuster & Reyes- Castillo 1990, O. quichensis Schuster & Reyes-Castillo 1990 and O. politus (Hincks 1953) (Guatemala). O. crassulus is redescribed and O. coxchicopi n. sp., O. monzoni n. sp., O. aluxi n. sp. and O. nahuali n. sp. are described, all species from cloud forests between 900 and 2064m altitude in Guatemala and Honduras. A key to the species of Ogyges is given.